1991
DOI: 10.1111/j.1365-2249.1991.tb05817.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of hyperbaric oxygenation on immune responses of normal and autoimmune mice

Abstract: We studied the effect of hyperbaric oxygenation (HBO) on immune responses in normal and autoimmune mice. Mice were exposed to HBO in an animal chamber at a pressure of 252.5 kPa for 1 h and once a day for 5 days. The immunization of C3H/He mice with sheep erythrocytes induced marked anti-sheep erythrocyte antibody response on day 7. However, this response was markedly suppressed in HBO-treated mice. The suppression is dependent on the duration of HBO and it works on the early and the late stage of antibody res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…In the present study, it is not clear if alleviated inflammation is due to reduced TNF-α and IL-1β production or reduction of TNF-α and IL-1β is secondary to reduced inflammation. Moreover, the immunomodulatory effect of HBO 2 , involving altered cytokine release by macrophages [36,37], including an immunosuppressive effect of HBO 2 [38], has been described. The present study suggests that the reduction of IL-1 production may play an important role in the immunosuppressive effect of HBO 2. Several factors seem to be important in the pathogenesis of INDO-induced intestinal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it is not clear if alleviated inflammation is due to reduced TNF-α and IL-1β production or reduction of TNF-α and IL-1β is secondary to reduced inflammation. Moreover, the immunomodulatory effect of HBO 2 , involving altered cytokine release by macrophages [36,37], including an immunosuppressive effect of HBO 2 [38], has been described. The present study suggests that the reduction of IL-1 production may play an important role in the immunosuppressive effect of HBO 2. Several factors seem to be important in the pathogenesis of INDO-induced intestinal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Such a concept was proposed by Saito et al as early as 1991 [6], which was repeatedly experimentally confirmed over the following decades [17,23,44,45], with some researchers suggesting the possibility of using hyperbaric oxygen therapy in the treatment of autoimmune diseases. [6,7,46,47,48].…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…[6,7,46,47,48]. Interestingly, one of the studies demonstrated that even an increased ambient pressure alone, without additional oxygenation of the breathing mix or its replacement with O2 also led to a reduction of TNF-α levels in experimental animals [24].…”
Section: Research Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations